Chronic Neurobehavioral Sex Differences in a Murine Model of Repetitive Concussive Brain Injury - Tucker, Laura B.; Velosky, Alexander G.; Fu, Amanda H.; McCabe, Joseph T. (Frontiers in Neurology, 2019)
Traumatic brain injury (TBI) resulting from repeated head trauma is frequently characterized by diffuse axonal injury and long-term motor, cognitive and neuropsychiatric symptoms. Given the delay, often decades, between repeated head traumas and the presentation of symptoms in TBI patients, animal models of repeated injuries should be studied longitudinally to properly assess the longer-term effects of multiple concussive injuries on functional outcomes. In this study, male and cycling female C57BL/6J mice underwent repeated (three) concussive brain injuries (rCBI) delivered via a Leica ImpactOne cortical impact device and were assessed chronically on motor (open field and rotarod), cognitive (y-maze and active place avoidance) and neuropsychiatric (marble-burying, elevated zero maze and tail suspension) tests. Motor deficits were significant on the rotarod on the day following the injuries, and slight impairment remained for up to six months. All mice that sustained rCBI had significant cognitive deficits on the active place avoidance test and showed greater agitation (less immobility) in the tail suspension test. Only injured male mice were significantly hyperactive in the open field, and had increased time spent in the open quadrants of the elevated zero maze. One year after the injuries, mice of both sexes exhibited persistent pathological changes by the presence of Prussian blue staining (indication of prior microbleeds), primarily in the cortex at the site of the injury, and increased GFAP staining in the perilesional cortex and axonal tracts (corpus callosum and optic tracts). These data demonstrate that a pathological phenotype with motor, cognitive and neuropsychiatric symptoms can be observed in an animal model of rCBI for at least one year post-injury, providing a pre-clinical setting for the study of the link between multiple brain injuries and neurodegenerative disorders. Furthermore, this is the first study to include both sexes in a pre-clinical long-term rCBI model, and female mice are less impaired functionally than males.